Community participation: Rhectoric or reality? - Raniga, T; Simpson, B (Social Work/Maatskaplike Werk, 2002)
Central to any conununity development project is the notion of community participation and there is widespread agreement that community participation is an essential feature of any community development initiative. It is argued, almost as a matter of course, that people should be involved in identifying their needs and problems and in finding appropriate solutions. The term "community participation", however, has come to mean many things to many people and remains an ill-defined term. It "has popularity without clarity, and is subject to growing faddishness and a lot of lip service" (De Kadt, 1982:574). Written in 1982, this comment still has relevance today as social workers and community development personnel struggle to put the principles of community participation into practice. This paper examines community participation in relation to an abortive attempt to establish a community garden project in an informal settlement. Examining what went wrong in this project and making suggestions for avoiding these problems in the future will hopefully contnbute to improved intervention strategies. The paper begins with a brief overview of the literature concerning community participation and highlights some of the difficulties associated with its definition. This provides the context for understanding community participation in the garden project. It then describes the community garden project and outlines the research process that was used to evaluate community participation in this project. The results of this research study revealed that, although community participation was valued in principle, its practical application was lacking. Reasons for this are advanced and the implications of this for practice are discussed.